Answer:
We can place everything with v(x) on one side of the equality, everything with x on the other side. This is done on the step-by-step explanation, and shows that the new equation is separable.
Step-by-step explanation:
We have the following differential equation:
![xy' = y(ln x - ln y)](https://tex.z-dn.net/?f=xy%27%20%3D%20y%28ln%20x%20-%20ln%20y%29)
We are going to apply the following substitution:
![y = xv(x)](https://tex.z-dn.net/?f=y%20%3D%20xv%28x%29)
The derivative of y is the derivative of a product of two functions, so
![y' = (x)'v(x) + x(v(x))'](https://tex.z-dn.net/?f=y%27%20%3D%20%28x%29%27v%28x%29%20%2B%20x%28v%28x%29%29%27)
![y' = v(x) + xv'(x)](https://tex.z-dn.net/?f=y%27%20%3D%20v%28x%29%20%2B%20xv%27%28x%29)
Replacing in the differential equation, we have
![xy' = y(ln x - ln y)](https://tex.z-dn.net/?f=xy%27%20%3D%20y%28ln%20x%20-%20ln%20y%29)
![x(v(x) + xv'(x)) = xv(x)(ln x - ln xv(x))](https://tex.z-dn.net/?f=x%28v%28x%29%20%2B%20xv%27%28x%29%29%20%3D%20xv%28x%29%28ln%20x%20-%20ln%20xv%28x%29%29)
Simplifying by x:
![v(x) + xv'(x) = v(x)(ln x - ln xv(x))](https://tex.z-dn.net/?f=v%28x%29%20%2B%20xv%27%28x%29%20%3D%20v%28x%29%28ln%20x%20-%20ln%20xv%28x%29%29)
![xv'(x) = v(x)(ln x - ln xv(x)) - v(x)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28ln%20x%20-%20ln%20xv%28x%29%29%20-%20v%28x%29)
![xv'(x) = v(x)((ln x - ln xv(x) - 1)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28%28ln%20x%20-%20ln%20xv%28x%29%20-%201%29)
Here, we have to apply the following ln property:
![ln a - ln b = ln \frac{a}{b}](https://tex.z-dn.net/?f=ln%20a%20-%20ln%20b%20%3D%20ln%20%5Cfrac%7Ba%7D%7Bb%7D)
So
![xv'(x) = v(x)((ln \frac{x}{xv(x)} - 1)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28%28ln%20%5Cfrac%7Bx%7D%7Bxv%28x%29%7D%20-%201%29)
Simplifying by x,we have:
![xv'(x) = v(x)((ln \frac{1}{v(x)} - 1)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28%28ln%20%5Cfrac%7B1%7D%7Bv%28x%29%7D%20-%201%29)
Now, we can apply the above ln property in the other way:
![xv'(x) = v(x)(ln 1 - ln v(x) -1)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28ln%201%20-%20ln%20v%28x%29%20-1%29)
But ![ln 1 = 0](https://tex.z-dn.net/?f=ln%201%20%3D%200)
So:
![xv'(x) = v(x)(- ln v(x) -1)](https://tex.z-dn.net/?f=xv%27%28x%29%20%3D%20v%28x%29%28-%20ln%20v%28x%29%20-1%29)
We can place everything that has v on one side of the equality, everything that has x on the other side, so:
![\frac{v'(x)}{v(x)(- ln v(x) -1)} = \frac{1}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bv%27%28x%29%7D%7Bv%28x%29%28-%20ln%20v%28x%29%20-1%29%7D%20%3D%20%5Cfrac%7B1%7D%7Bx%7D)
This means that the equation is separable.